2005
DOI: 10.1002/ajhb.20410
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption (Hair Mercury) and nutritional status of Amazonian Amer-Indian Children

Abstract: Fish are abundant and important dietary items for the Amer-Indians, and total hair-Hg (HHg) concentration is a reliable marker of fish consumption. We studied the impact of fish consumption (HHg) on the nutritional status of Indian children of Eastern Amazonia. Weight-for-height Z score (WHZ) was measured, and HHg was determined in 203 children younger than 10 years of age in three villages. There was significantly higher fish consumption in Kayabi children (16.55 microg Hg/g; SD, 11.44) than in children of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 40 publications
2
26
1
6
Order By: Relevance
“…In another paper, the same team tried to demonstrate a positive effect on growth of fish consumption, judged from H-Hg. They failed to demonstrate a consistent pattern as we did here (Dorea et al 2005a). This may be due to the fact that they did not segregate their population into different age groups.…”
Section: Discussioncontrasting
confidence: 35%
“…In another paper, the same team tried to demonstrate a positive effect on growth of fish consumption, judged from H-Hg. They failed to demonstrate a consistent pattern as we did here (Dorea et al 2005a). This may be due to the fact that they did not segregate their population into different age groups.…”
Section: Discussioncontrasting
confidence: 35%
“…It has been shown previously that among native Amazonian tribes, differences in the rate of fish consumption (127 g fish/d v. 30 g fish/d) were compensated by other protein sources that showed no significant correlation with the attained growth of Amer-Indian children (27) . Subsequent studies with an urban Amazonian population indicated that the habitual dominance of fish consumption, although important for some nutrients, can be successfully replaced by other animal food sources (28) .…”
mentioning
confidence: 89%
“…Existem estudos onde é sugerido que os níveis de Hg em cabelo podem ser um indicador da frequência de consumo de peixe (Dórea et al, 2005 Embora os resultados dos estudos sejam contraditórios, se reconhece que o metilmercúrio é uma substância de alto risco para crianças, por ser capaz de atravessar a barreira hematoencefálica e transplacentária (Who, 1990) Consequentemente, a exposição pode começar na etapa da gestação, através da alimentação da mãe, e atingir o sistema nervoso central da criança, que está em desenvolvimento nesse momento, podendo assim, causar danos irreversíveis no feto, embora a mãe não apresente sintomas de intoxicação (Counter e Buchanan, 2004;Davidson et al, 2004;Crespo-Lópeza et al, 2005;Mergler et al, 2007).…”
Section: Estudos De Exposição De Mercúrio Em Criançasunclassified